Social Knowledge: The Study of Three Processes of Metamorphosis - Ghoreishi, Fardin (Journal of History Culture and Art Research, 2017)
Social knowledge is more dynamic than natural science. A full recognition of this character is the precondition for upholding the validity of statements in social knowledge. In order to maintain the validity of such statements and to avoid the metamorphosis of social knowledge into other theoretical constructs, this paper, based on referring to the ideal type of social knowledge, aims to describe and explain three processes whereby social knowledge is metamorphosed into theoretical dogmatism, theoretical alienation, and theoretical slavery.